Macrophages and platelets in liver fibrosis and hepatocellular carcinoma - Casari, Martina; Siegl, Dominik; Deppermann, Carsten; Schuppan, Detlef (Frontiers in Immunology, 2023)
During fibrosis, myofibroblasts deposit large amounts of extracellular matrix proteins, thereby replacing healthy functional tissue. In liver fibrosis, this leads to the loss of hepatocyte function, portal hypertension, variceal bleeding, and increased susceptibility to infection. At an early stage, liver fibrosis is a dynamic and reversible process, however, from the cirrhotic stage, there is significant progression to hepatocellular carcinoma. Both liver-resident macrophages (Kupffer cells) and monocyte-derived macrophages are important drivers of fibrosis progression, but can also induce its regression once triggers of chronic inflammation are eliminated. In liver cancer, they are attracted to the tumor site to become tumor-associated macrophages (TAMs) and polarize towards an M2-type anti-inflammatory/tumor-promoting phenotype. Besides their role in thrombosis and hemostasis, platelets can also stimulate fibrosis and tumor development by secreting profibrogenic factors and regulating the innate immune response, e.g., by interacting with monocytes and macrophages. Here, we review recent literature on the role of macrophages and platelets and their interplay in liver fibrosis and hepatocellular carcinoma.